Boganmeldelser - Stevnsborg, Henrik; Nielsen, Beth Grothe; Gabrielsen, Gorm; Kyvsgaard, Britta; Papendorf, Knut; Stangeland, Per; Greve, Vagn (Nordisk Tidsskrift for Kriminalvidenskab, 1986)
Book reviews